2016
DOI: 10.1007/s11739-016-1508-5
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of two different tolvaptan doses in the treatment of hyponatremia in the Emergency Department

Abstract: Hyponatremia (plasma sodium concentration or [Na] <136 mEq/L) is the most common electrolyte unbalance in clinical practice. Although it constitutes a negative prognostic factor, it frequently remains underdiagnosed and undertreated. Tolvaptan is an oral V-receptor antagonist which produces aquaresis. Given its emerging role in the treatment of dilutional hyponatremia, we aimed to compare the efficacy and safety of two different doses of this drug in an Emergency Department (ED) setting. Consecutive patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 41 publications
1
24
0
Order By: Relevance
“…In contrast, the group receiving TLV 7.5 mg dose had a median increase in serum sodium of 6 mmol/L (range, 1–11 mmol/L). Castello et al 23 also found that in patients with lower starting levels of serum sodium there was a tendency to see larger increases in serum sodium levels. The authors concluded that a daily dose of 7.5 mg TLV was both effective and safe, whereas 15 mg TLV had a high risk of overcorrection.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In contrast, the group receiving TLV 7.5 mg dose had a median increase in serum sodium of 6 mmol/L (range, 1–11 mmol/L). Castello et al 23 also found that in patients with lower starting levels of serum sodium there was a tendency to see larger increases in serum sodium levels. The authors concluded that a daily dose of 7.5 mg TLV was both effective and safe, whereas 15 mg TLV had a high risk of overcorrection.…”
Section: Discussionmentioning
confidence: 91%
“…Two small studies have focused on the overcorrection of serum sodium within the first 24 hours of treatment with 15 mg TLV in patients with hypervolemic or euvolemic hyponatremia. 23 24 Castello et al 23 investigated the efficacy and safety of two different doses of TLV (7.5 and 15 mg) in patients with hypervolemic and euvolemic hyponatremia and reported that the group receiving TLV 15 mg showed a median increase in serum sodium of 12 mmol/L (range, 6–25 mmol/L) and this correction rate exceeded the values recommended by recent guidelines in 75% of patients, although no ODS was reported. In contrast, the group receiving TLV 7.5 mg dose had a median increase in serum sodium of 6 mmol/L (range, 1–11 mmol/L).…”
Section: Discussionmentioning
confidence: 99%
“…Although conventional diuretics, particularly furosemide, decrease the serum level of Na, tolvaptan increases free water excretion without introducing major systemic electrolyte loss. Instead, the serum Na concentration increases dose-dependently ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our research group essentially agrees with this final statement, particularly if copeptin levels are obtained in an emergency medicine context. In fact, in the last few years we carried out many studies focused on the diagnosis and treatment of hyponatremia in the ED [ 17 , 18 ]. For example, data we obtained from 22 patients with hypovolemic hyponatremia confirmed the wide variability of copeptin levels even in the same subgroup of patients (IQR 9.71–100.95 pmol/L) [ 18 ].…”
mentioning
confidence: 99%
“…Unpublished data obtained from a secondary analysis of 18 euvolemic and hypervolemic patients with hyponatremia enrolled in another ED trial [ 17 ], once again demonstrates a wide variability in copeptin levels without significant differences between euvolemic and hypervolemic patients.…”
mentioning
confidence: 99%